PKM kelompok guru SMK melalui pelatihan Microcontroller Skills for Cyber Physical System di SMK Negeri 4 Gowa - Yasser Abd. Djawad; Sutarsi Suhaeb; Mantasia Mantasia (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The Community Partnership Program (PKM) partner is the SMK 4 Gowa Department of Electronic Audio Video Engineering. Industrial Revolution 4.0 requires scientists, academics, and practitioners to emphasize the patterns of digital economy, artificial intelligence, internet of things, and big data. The problem is that there is still a lack of insight and knowledge of teachers and students about the Internet of Things (IoT) so that it is done Microcontroller Skills for Cyber Physical System training. The method used is: seminars and workshops. The results achieved are (1) Teachers of SMK Negeri 4 Gowa have the knowledge and can apply the Work Skill Microcontroller Skills For Cyber Physical System, IoT, and Cloud properly. (2) Teachers of State Vocational School 4 Gowa can apply learning related to the concept of industry 4.0. (3) Teachers of SMK Negeri 4 Gowa can create independent works so they can become good craftsmanship through a microcontroller media trainer and IoT Interface.